Experimental investigation of the tensile behavior and acoustic emission characteristics of anisotropic shale under geothermal environment. (15th January 2023) - Guo, Yide; Huang, Linqi; Li, Xibing
Abstract: Shale gas is becoming a top priority for future global energy consumption and climate change mitigation, and deep and ultradeep shale gas extraction cannot overlook the influence of the geothermal environment. This paper experimentally investigated the tensile behavior and acoustic emission (AE) characteristics of anisotropic shale under geothermal environment of 25–200 °C. The results indicate that the tensile strength and absorbed energy of all specimens decreased with increasing temperature, and minimum values occurred in specimens with a layer inclination of 90° at each temperature. The evolution of tensile strength and absorbed energy versus the layer inclination did not vary with increasing temperature, exhibiting an inverted-V shape. Anisotropic failure mode of specimens with layer inclinations of 30°, 45° and 60° was influenced by the increasing temperature, but central tensile fracturing in specimens with layer inclinations of 0° and 90° was temperature-independent. With increasing temperature, the cumulative AE hits of specimens showed a highly obvious step-up trend, and anisotropic crack initiation stress levels obtained via the AE definition significantly varied. Finally, microstructure response, fracture length and fracture location and proportion of fracture types were discussed, and potential applications and challenges of geothermal environment in hydraulic fracturing of deep shale reservoirs were proposed. Highlights: Tensile behavior and AE characteristics of shale under the geothermal environment were investigated by Brazilian test. Anisotropic tensile properties and AE activities of shale specimens versus the geothermal temperature were summarized. Anisotropic failure behavior of shale specimens versus the geothermal temperature was concluded and discussed. Potential applications of geothermal environment in hydraulic fracturing of deep shale reservoirs were proposed.